TEACHER'S STRATEGIES IN OVERCOMING LEARNING BARRIERS IN EFL CLASSROOM - Pakpahan, Sirintin; Azeva, Dian Zahira; Simanjuntak, Azzura Annisa; Herlina, Herlina; Bahri, Dwi Ichwanul; Deswandra, Ilham; Dewi, Desi Surlitasari; Sugiharti, Sri; Abra, Emy Hajar; Perwira, Andika (Universitas Riau Kepulauan, 2024)
The purpose of this study is to identify the strategies that EFL teachers use to overcome learning barriers in the classroom. A mixed methods approach was used to collect data through a Likert-scale questionnaire with 30 teachers and interviews with three teachers from various regions in Indonesia. Quantitative findings revealed that teachers frequently employed strategies such as differentiated instruction, motivational support, and digital media integration. Through thematic coding, the qualitative analysis further revealed specific techniques, including simplifying materials, employing collaborative learning, managing student focus, and encouraging passive learners through praise and rapport building. These results underscore the importance of adaptive, student-centered teaching practices for addressing the diverse challenges in EFL classrooms. The study suggests that a combination of cognitive, emotional, and technological strategies is essential for improving learning outcomes.